Narratives from the Margins: The Representation of the Migrant Child, Space, and Gender Violence in Three Peruvian Short Stories - Manrique Rabelo, Carlos Milton; Rodriguez Narvaez, Vanessa; Rivas Sucari, Henry César; Mere Collazos, Milagros Jessica (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This paper aims to reading on the representation of the migrant-child subject, space and gender violence in three Peruvian stories: “El ñiño de Junto al Cielo” (1954) by Enrique Congrains Martín, “Montacerdos” (1981) by Cronwell Jara Jiménez, and “Brisas III” (2015) by Gerónimo Chuquicaña Saldaña. For this, a comparative, descriptive-interpretive study was carried out on the selected stories. Likewise, the categories migrant subject and heterogeneity proposed by Antonio Cornejo Polar, the types of narrator and focalization according to Mieke Bal and Gerard Genette, and the studies on gender by Pierre Bourdieu, Judith Butler and Norma Fuller were taken place. The analysis and interpretation will demonstrate that factors such as spatial context, marginalization, and gender violence significantly influence the migrant status and identity of the child protagonists in these narratives. These influences render them susceptible to violence, vulnerability, and insecurity.